Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1108/ijqrm-07-2019-0244
|View full text |Cite
|
Sign up to set email alerts
|

The impact of lean manufacturing practices on operational and financial performance: the mediating role of agile manufacturing

Abstract: PurposeThis empirical study aims to explore the link between lean manufacturing practices (total quality management, just-in-time production, just-in-time purchasing, total productive/preventive maintenance), agile manufacturing, and operational and financial performance.Design/methodology/approachData were collected from 205 Tunisian manufacturing firms, and the results were analyzed using structural equation modeling.FindingsThe results indicate that (1) lean manufacturing practices have a direct positive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 77 publications
(183 reference statements)
2
75
1
1
Order By: Relevance
“…A road map was developed by Talib et al ( 2020 ) to help DM to facilitate the successful implementation of the integrated JIT-LPs to improve the performance of the Indian manufacturing industries using BWM. Khalfallah and Lakhal ( 2020 ) empirically explored the link between LMPs, AM, and operational and financial performance in 205 Tunisian manufacturing firms. The results showed that, except for JIT production, LMP had a direct positive relationship with AM, (2) AM had a positive impact on OP, and (3) LMP did not seem to contribute directly to OP.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A road map was developed by Talib et al ( 2020 ) to help DM to facilitate the successful implementation of the integrated JIT-LPs to improve the performance of the Indian manufacturing industries using BWM. Khalfallah and Lakhal ( 2020 ) empirically explored the link between LMPs, AM, and operational and financial performance in 205 Tunisian manufacturing firms. The results showed that, except for JIT production, LMP had a direct positive relationship with AM, (2) AM had a positive impact on OP, and (3) LMP did not seem to contribute directly to OP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Holweg ( 2007 ), LMP is an operational practice that creates value for the customers and eliminates waste with the spending resources. Khalfallah and Lakhal ( 2020 ) in an empirical study on Tunisian 205 manufacturing firms’ LMP on operational performance showed that LMP contributed to operational performance through the mediation of agile manufacturing. The Lean assessment conducted by Ibrahim et al ( 2020 ) on the Malaysian construction industry revealed a relationship between LMP and OP.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggest that the five major agile competencies include transparent customization supply chains of agile nature, automation, employee empowerment and technology integration. Khalfallah and Lakhal (2020)…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to achieve the aforesaid, the driving force behind the concept of agile manufacturing pivots on the following points, as described by Yusuf et al (1999): It is a well-known fact that holistic lean manufacturing implementation requires 3-5 years, and requires top management commitment, employee training and embracing the lean thinking approach. Similarly, the literature review suggested that in case of agile manufacturing, the successful implementation is incumbent upon the top management commitment to achieve higher operational performance (Khalfallah & Lakhal, 2020). Therefore, a conscious effort should be made towards integrated implementation of both approaches for optimized manufacturing and operational performances.…”
Section: Using Agile Tool Of Technological Unificationmentioning
confidence: 99%